Persepsi Guru PJOK terhadap Pelaksanaan Kurikulum Merdeka pada Mata Pelajaran PJOK - Setyawan, Risfandi; Pradana, Rendra Wahyu (MAN Insan Cendekia Jambi, 2024)
The purpose of this study was to determine the perception of PJOK teachers towards the implementation of the Merdeka curriculum in PJOK subjects. The research design is descriptive qualitative, the population in this study were all PJOK teachers of Jombang State High School, totalling 2 teachers. sampling method with Purposive Sampling. Research instruments with a question with an interview with each PJOK educator. There are 30 questions with 2 aspects of the indicator. Data analysis carried out is data presentation, and conclusion drawing. The results of research related to indicators of knowledge and readiness of the results of the explanation are quite good and indicators of the obstacles and impact of the independent curriculum on PJOK learning with a good response will make the implementation of the independent curriculum well. The conclusion of the knowledge and readiness indicators is quite good, for the impact and obstacles students give a good response to the form of application of the independent curriculum by the PJOK teacher has been successful.